Molecular epidemiology and virulence factors of pyogenic liver abscess causing Klebsiella pneumoniae in China. (14th June 2014) - Luo, Y.; Wang, Y.; Ye, L.; Yang, J.; Grobusch, M.
Abstract The molecular epidemiology and prevalence of virulence factors of isolates from patients with Klebsiella pneumoniae liver abscess (KLA) in mainland China are unknown. Klebsiella pneumoniae isolates were obtained from drainage samples aseptically collected from patients with pyogenic liver abscess (PLA). The genetic similarity of KLA isolates was analyzed by pulsed‐field gel electrophoresis. The hypermucoviscosity (HV) phenotype was identified by a positive string test. The K1 and K2 genotypes, the pLVPK‐derived genetic loci, aerobactin gene, kfu and alls were detected by PCR amplification. The sequence types (STs) were identified by multilocus sequence typing. Among the 51 non‐repetitive KLA isolates, 49 PFGE types have been identified. In total, 19 (37.2%) and 14 (27.4%) of the 51 KLA isolates belonged to clonal complex (CC) 23 and CC65, respectively, while the other 18 isolates (35.3%) were defined as other STs. CC23 consisted of only K1 strains, while CC65 included only K2 strains. All non‐K1/K2 strains were classified as STs other than CC23 and CC65. Approximately 70.6% (36/51) of KLA isolates exhibited an HV phenotype. Both K1 and K2 isolates presented significantly higher prevalence of the pLVPK‐derived loci than non‐K1/K2 isolates. The K1 isolates had a significantly higher prevalence of the kfu and allS genes than K2 and non‐K1/K2 isolates, while the K2 isolates exhibited higher repA prevalence than K1 and non‐K1/K2 isolates. The majority of KLA isolates belonged to CC23K1 and CC65K2, while other STs with non‐K1/K2 capsular types have also been identified. The virulent factors exhibited diverse distribution among the different clones of KLA isolates.